Patient's experience of treatment for sleep apnoea with a mandibular advancement splint. Issue 5 (October 2015) - Bhamrah, Gurprit; Dhir, Arti; Cash, Alex; Ahmad, Sofia; Winchester, Lindsay J.
Abstract Background and aims Obstructive sleep apnoea (OSA) is a well recognised clinical disorder in which there is narrowing and repeated collapse of the upper airway during sleep resulting in the cessation of breathing. Patients with mild to moderate sleep apnoea are often provided with mandibular advancement splint (MAS) therapy as a form of first line or definitive treatment. The aims of this audit were to evaluate patient satisfaction and success of MAS therapy. Methods 93 patients diagnosed with sleep apnoea and suitable for a splint were recruited prospectively at Queen Victoria Hospital, East Grinstead between January 2009 and October 2010. A patient satisfaction questionnaire was developed by health professionals involved in the care of patients with sleep apnoea and assessed for face and content validity and reliability. Participants completed the questionnaire six weeks after the splint was fitted. Results 44% who previously experienced snoring now reported no snoring and 47% reported less snoring since wearing the MAS appliance. 69% reported complete resolution of sleep apnoea symptoms. 37% experienced aching teeth and 33% experienced having a dry throat when wearing the appliance. 86% of sleeping partners felt that their quality of sleep was improved following their partners treatment. Conclusions The standards set for each criteria in this audit were met. MAS treatment has a key role to play in the management of obstructive sleep apnoea with high rates of patient satisfaction and the majority of patients partners reporting a significant improvement in their own and their partners sleep quality.